(untitled) (Al-Academy, 2019)
Most of the cinema and television production relies on the use of modern digital technologies, which today become the as ideal as the artistic expressive style that sends aesthetic values ​​through the use of electronic elements of the language of cinema and television to achieve aesthetic dazzling, and design the digital production for the purpose of persuasion, as well as the use of digital effects and graphics to activate the aesthetic pleasure. The research tries to subject all these aspetcs to study and apply them to a modern sample in order to get the results that confirm this technical and artistic aesthetic synergy that leads to the emergence of a cinema and television achievement the least to say about it is that it is beautiful